Design, synthesis and docking studies of novel thiazole derivatives incorporating pyridine moiety and assessment as antimicrobial agents - Khidre, Rizk E.; Radini, Ibrahim Ali M. (Scientific reports, 2021)
A novel series of substituted 4,6-dimethyl-2-oxo-1-(thiazol-2-ylamino)-1,2-dihydropyridine-3-carbonitrile derivatives 6 , 9 , 13 , 15 , and 17 was synthesized in a good to excellent yield from the reaction of 1-(3-cyano-4,6-dimethyl-2-oxopyridin-1(2 H )-yl)thiourea with 2-oxo- N '-arylpropanehydrazonoyl chloride, chloroacetone, α -bromoketones, ethyl chloroacetate, and 2,3-dichloroquinoxaline, respectively. The potential DNA gyrase inhibitory activity was examined using in silico molecular docking simulation. The novel thiazoles exhibit dock score values between − 6.4 and − 9.2 kcal/mol and they were screened for their antimicrobial activities. Compound 13a shown good antibacterial activities with MIC ranged from 93.7–46.9 μg/mL, in addition, it shown good antifungal activities with MIC ranged from 7.8 and 5.8 μg/mL.